Experimenting With a Digital Application to Codesign Ikat Textile Patterns With Weaving Community - Warin Boonyaputthipong; Disaya Chudasri; Patison Palee; Thomas Gilsdorf (Human Behavior and Emerging Technologies, 2026)
This article presents a multidisciplinary research project that involves a digital application developed for ikat weaving communities from Chonnabot District in Khon Kaen Province in Thailand. The app is aimed at generating new pattern designs based on traditional textile patterns and that correlate to weaving cultures. The structure of this article is as follows. First, it explains digitization and cultural heritage, followed by ikat weaving, a cultural heritage of the Chonnabot district, and the traditional skirt and changes to reed′s width. Second, research methodology is discussed, comprising two main tasks: designing patterns and making mudmee fabrics. We also explain a reason for applying a mathematical theory, specifically frieze group, as a set of rules to generate patterns, and outline the main steps for using the app. Third, we present results, including virtual pattern designs and real woven fabrics, and assessment of the app′s usability. Next, we discuss feedback from the participants as well as the weavers′ behavior in relation to the app′s usability and weaving, along with suggestions for improving the app. We conclude that the app is useful and has potential for teaching and learning for textile design courses. However, the app needs further development to correspond with the weavers′ view on the ikat weaving process. Overall, this collaborative project, including design and weaving tasks, enables knowledge exchange and is beneficial for design students and weavers as well as supports their livelihood.
Keywords: Crafts, Textile, and Design; Fashion and Cultural Textiles; Art, Technology, and Culture